Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To find the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] given the pair of equations [tex]\( (2x + y, x - 2y) = (3, 4) \)[/tex], follow these steps:
1. Set up the system of equations based on the given pairs:
[tex]\[ 2x + y = 3 \][/tex]
[tex]\[ x - 2y = 4 \][/tex]
2. Solve the system of equations simultaneously:
First, take the two equations:
[tex]\[ \text{Equation 1: } 2x + y = 3 \][/tex]
[tex]\[ \text{Equation 2: } x - 2y = 4 \][/tex]
Step 1: Solve Equation 2 for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ x = 4 + 2y \][/tex]
Step 2: Substitute [tex]\( x \)[/tex] from Equation 2 into Equation 1:
[tex]\[ 2(4 + 2y) + y = 3 \][/tex]
Simplify the equation:
[tex]\[ 8 + 4y + y = 3 \][/tex]
Combine like terms:
[tex]\[ 8 + 5y = 3 \][/tex]
Step 3: Solve for [tex]\( y \)[/tex]:
[tex]\[ 5y = 3 - 8 \][/tex]
[tex]\[ 5y = -5 \][/tex]
[tex]\[ y = -1 \][/tex]
Step 4: Substitute [tex]\( y = -1 \)[/tex] back into Equation 2 to find [tex]\( x \)[/tex]:
[tex]\[ x = 4 + 2(-1) \][/tex]
Simplify:
[tex]\[ x = 4 - 2 \][/tex]
[tex]\[ x = 2 \][/tex]
Therefore, the values are:
[tex]\[ x = 2 \quad \text{and} \quad y = -1 \][/tex]
1. Set up the system of equations based on the given pairs:
[tex]\[ 2x + y = 3 \][/tex]
[tex]\[ x - 2y = 4 \][/tex]
2. Solve the system of equations simultaneously:
First, take the two equations:
[tex]\[ \text{Equation 1: } 2x + y = 3 \][/tex]
[tex]\[ \text{Equation 2: } x - 2y = 4 \][/tex]
Step 1: Solve Equation 2 for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ x = 4 + 2y \][/tex]
Step 2: Substitute [tex]\( x \)[/tex] from Equation 2 into Equation 1:
[tex]\[ 2(4 + 2y) + y = 3 \][/tex]
Simplify the equation:
[tex]\[ 8 + 4y + y = 3 \][/tex]
Combine like terms:
[tex]\[ 8 + 5y = 3 \][/tex]
Step 3: Solve for [tex]\( y \)[/tex]:
[tex]\[ 5y = 3 - 8 \][/tex]
[tex]\[ 5y = -5 \][/tex]
[tex]\[ y = -1 \][/tex]
Step 4: Substitute [tex]\( y = -1 \)[/tex] back into Equation 2 to find [tex]\( x \)[/tex]:
[tex]\[ x = 4 + 2(-1) \][/tex]
Simplify:
[tex]\[ x = 4 - 2 \][/tex]
[tex]\[ x = 2 \][/tex]
Therefore, the values are:
[tex]\[ x = 2 \quad \text{and} \quad y = -1 \][/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.